Optimal and Economic Programming in a Reconfigured Competitive Electricity Market Considering Dispersed Generation Sources with the Firefly Algorithm - Muhammad Sibtain; Snoober Saleem (Advances in Engineering and Intelligence Systems)
Nowadays, the majority of electric energy demand in different countries is supplied by using fossil fuels. As fossil energies are non-renewable and cause environmental pollution, the use of renewable energy sources (RES) is essential for supplying electric energy. Due to the fluctuations in RES, dispersed generation (DG) units are used as microgrids (MGs) to prevent problems in supplying the energy demanded by customers. Here, a novel two-phase method is proposed to simultaneously find the optimal location and operation of DGs. In phase 1, the DG location problem is formulated as a multi-objective problem, aiming to reduce active power losses, improve voltage profile, and increase voltage. This multi-objective problem is solved by using the firefly optimization algorithm, and the optimal DG location is determined. In phase 2, the revenues of DG owners and the total payment of the distribution network (DN) are calculated. The optimal sales prices of the units are also calculated by the game theory. The proposed method is implemented on a 33-bus system in MATLAB, and its results are compared with PSO and GA results to demonstrate the efficiency.